Estudo de modelagem e simulação sobre a produção de hidrogênio por eletrólise alcalina e sua conversão para metanol - Oliveira, Vitória Natasha Silva (2024)
In the face of the urgency to combat global warming and reduce dependence on fossil fuels, the search for renewable energy sources has become imperative. In this context, hydrogen has emerged as a promising energy vector, offering a solution to the challenges associated with the energy transition in a clean and efficient way. This study focused on the sustainable production of hydrogen through alkaline electrolysis and its subsequent conversion into methanol. For this purpose, an alkaline electrolyzer model, based on previous studies and adapted from literature, was described, implemented in Python and integrated into the DWSIM © simulator for comprehensive sensitivity and optimization analyses of the plant. In addition to hydrogen production, the conversion of this compound into methanol was explored as a strategic solution to the challenges of hydrogen storage and transport to increase energy density. The investigation addressed the rate laws governing the reactions in the hydrogenation of polluting gases into methanol. The objective was to compare the kinetic models of Bussche-Froment and Graaf models, which are used without a clear preference, seeking to discuss and identify the predominant factors influencing process efficiency. The validation of the implementation of the models for hydrogen and methanol production revealed experimental deviations of less than 10%. The implementation developed in Python and DWSIM © proved useful for optimizing the electrolyzer construction, highlighting the potential improvement in electrolysis efficiency through bubble dispersion and demonstrated that Electrolyzer 1 ensures higher efficiencies. In the hydrogenation analysis, both models exhibited similar behaviors, although the values were significantly distinct, especially at low temperatures and high pressures for the analyzed composition. It was found that methanol production and CO 2 conversion were more abundant at temperatures between 200 and 250 °C. Increasing pressure contributed to greater methanol production. Raising the H 2 /CO 2 ratio favored gas conversion, reaching an average prediction form both models of 37% with an 8:1 ratio, but the ratio around 3:1 for Graaf model and 2:1 for BF model resulted in maximum methanol production. Finally, the increase in CO concentration elevated the obtained methanol concentration but resulted in a lower conversion of carbon dioxide.